Vitamin E is ineffective for symptomatic relief of knee osteoarthritis: a six month double blind, randomised, placebo controlled study - Brand, C (2001)
OBJECTIVE—There is a putative role for antioxidant treatment in osteoarthritis (OA) based on animal, epidemiological, and human clinical studies. Vitamin E, a fat soluble vitamin, is one of the major dietary antioxidants. Short term clinical studies using vitamin E in the form of α-tocopherol suggested a benefit over placebo of similar dimension to that of diclofenac for relief of OA pain. METHODS—A six month, double blind, randomised, placebo controlled study of vitamin E 500 IU/day was carried out. Primary outcome measures were pain, stiffness, and function. Statistical analysis was performed on an intention to treat basis. RESULTS—77 patients were included in the study. Vitamin E showed no benefit over placebo at one month, three months, or six months for any of the outcome measures. The placebo group had higher pain levels (p=0.15) and body mass index (p=0.03) at baseline, and lower pain levels (p=0.02) at completion of the study. Radiological score, exercise score, age, or antioxidant intake at baseline or six months did not differ between the groups. The reasons for the better performance of the placebo group are uncertain but may relate to the initially higher pain score and subsequent regression to the mean. CONCLUSIONS—Vitamin E shows no benefit for the management of symptomatic knee OA. The role of vitamin E in preventing OA progression is currently under investigation.